Structural behaviors evaluation of RC beam under frost damage – A methodology with meso-macro material/bond simulation and integrating into structural analysis. (1st March 2020) - Wang, Zhao; Hayashida, Hiroshi; Zhang, Dawei; Gong, Fuyuan; Ueda, Tamon
Highlights: A multi-scale methodology is proposed to evaluate the structural performance of RC beam under frost damage. Meso-macro simulations of deteriorated material and bond properties are conducted with RBSM. Degradation models of concrete and bond are proposed and integrated into structural analysis with FEM. Verification experiment is conducted which shows the reliability of the methodology. Abstract: The structural performance under freezing and thawing environment shows severe deterioration, which has drawn large attention recently. Usually the deterioration owing to frost damage could attribute to two parts: the degradation of concrete mechanical properties and the degradation of bond properties between concrete and rebars. In this paper, a systematic study was accomplished and a multi-scale structural evaluation methodology was proposed. The macroscale degradations of both concrete and bond properties were simulated and modeled using a mesoscale discrete analytical approach - Rigid Body Spring Method. The proposed constitutive relationships for damaged concrete and bond properties were adopted in Finite Element Method to conduct structural analysis with considering the temperature history during the freezing-thawing process. Finally, experiment was conducted to verify the stated multi-scale methodology where satisfactory agreements were found between the experiment and FEM analysis.